The Trade-Union Programme of "Enlightened Selfishness" - Cummings, John (Journal of Political Economy, 1907)
The philosophy of unionism today is regarded as complete and final, as absolutely established and unimpeachable-much as certain economic doctrines xvere regarded as being finally determined a half-century since. This sense of absolute finality and unimpeachability presaged for economic science immediate disintegration and general repudiation of doctrines, and the rewriting of the whole science. Other absolutely established social philosophies have experienced the same sudden and final disso,lutio,n. In fact, history teaches that absollutism, and consequent sensitiveness toi criticism, tolgether with a certain disposition to irrascibility, is histo,rically speaking, commonly symptomatic olf declining vitality in soicial institutions, as it is in the natural human body. T'rade-unioinism, certainly has noi occasion to rely upon any doctrine o,f infallibility to establish its power. On the contrary, it may safely, and might wisely, rely upon the strength of its own programme, upo,n the justness o,f its cause, and upon its record of achievement foir its maiin defense against detracto,rs-even against its honest-minded critics; but it has not chosen to do so,. It no,t only does nolt seek honest criticism of its programme but resents any implications of fallibility as essentially impio,us. In the minds olf labor leaders the programme of unionism is cha.racterized as one o,f "masterful and surpassing intelligence," and o,ne who, presumes to, criticize is assumed to, be insincere and regardless of the welfare o,f the toiling masses. A judge who issues an injunction distasteful to, olrganized labo,r, however exemplary and incoirruptible the life he may have led, becomes at once, ipso facto, a "capitalistic tool." T'he judge whoi refuses such an injunction is an "able and distinguished chancellor, a judge loved by all honest men, and feared by respectable criminals." The injunctio,n itself is an "outrageous, impudent, revolutionary invention of lawless plutocracy." T'he detective whoi runs down some